A method for testing metal corrosion resistance
By optimizing ion beam focusing and vacuum conditions in nanoion probes, combined with low temperature treatment, the problem of difficult to test the resistance of metal materials against decay is solved, and the rapid and accurate detection of the resistance of metal materials is achieved, and the stability of the analysis process is improved. Sex and accuracy.
Patent Information
- Application Number
- CN202411659588.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-11-20
AI Technical Summary
The prior art is difficult to effectively test and evaluate the resistance to erosion of metal materials, especially in nano-ion probes. The non-uniform heating and erosion of metal accessories by ion beams lead to problems with instability and accuracy of the analysis process.
By optimizing the conditional parameters of the nanoion probe analysis process, the ion beam can be vertically focused on the longitudinal direction of the metal sample, combined with low-temperature pretreatment and gradient vacuum control, the diffusion of the ion beam energy and the out-expansion of heat are reduced, and the regular "cube column"-shaped erosion pit.
Accurate and rapid detection of the anti-decant ability of different metal materials, and obtain the relative size of the anti-decant ability of metal materials, providing indicative significance for the selection of metal materials adapted to nanoion probes, simplifying the detection process and improving accuracy sex.
Smart Images

Figure CN119147566B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal exfoliation testing, and in particular to a method for testing and evaluating metal anti-exfoliation capability. Background Art
[0002] Metal materials are widely used in all walks of life. Different application scenarios have different requirements for the performance of metal materials. It is no longer normal to use a single performance of a metal material as a reference standard. The nano-ion probe is a secondary ion mass spectrometer. It is composed of different metal materials (such as molybdenum, copper, rhenium, iridium alloy, iron alloy, etc.) inside and outside. It can be said to be a body of steel. The choice of metal materials for specific parts depends on the corresponding functional requirements.
[0003] Nano-ion probes use ion sources to generate primary ions to bombard the sample surface and generate secondary ions for mass spectrometry analysis of elemental isotopes. Metal accessories in the ion optical path system are directly bombarded by high-energy ion beams. When the high-energy ion beam contacts the surface of the metal accessories, the kinetic energy of the mechanical impact of the ion beam is transferred to the metal atoms, causing some metal atoms to obtain sufficient kinetic energy to escape from the surface. Further cascade collisions between metal atoms will cause more metal atoms to be stripped off. In addition, in a high vacuum environment, most of the energy of the ion beam is transferred to the atoms of the metal accessories and stored in the accessories in the form of heat. Since the energy of the ion beam presents a three-dimensional Gaussian distribution, the metal accessories are heated by the non-uniform heating of the ion beam, causing local expansion, melting, and evaporation into the vacuum. In addition, the primary ion beams generated by different types of ion sources (such as oxygen ion sources, cesium ion sources, etc.) have different loss effects on metals. For example, the effect of the primary oxygen ion beam on metal accessories also includes oxidation. These processes ultimately cause the erosion of metal accessories. The erosion of metal parts by the ion beam directly affects the stability of the analysis process, the accuracy of the analysis results, and even the service life of the equipment. Therefore, corrosion-resistant metals are a major demand orientation for the material properties of nano-ion probe accessories. Since the ion beam erosion of metal materials is a comprehensive process of physical change and chemical reaction, the selection of metals with good corrosion resistance requires comprehensive consideration of the mechanical properties, chemical properties and physical properties of metal materials. The evaluation of these properties requires the use of multiple detection methods, which is not only inefficient, but also has no direct indicators to characterize the corrosion resistance of metal materials under different ion beam conditions. In addition, since the metal surface is prone to irregular corrosion space during the bombardment of the metal by the oxygen ion source, it is necessary to comprehensively consider the width scanning area and the vertical depth, and go through a complex calculation process to accurately test the corrosion resistance of different metals. Summary of the invention
[0004] In view of the shortcomings of the prior art, the present invention proposes a method for detecting the anti-corrosion performance of metals. By optimizing the condition parameters of the nano-ion probe analysis process, the primary ion beam can be vertically focused on the longitudinal direction of the metal sample, avoiding the problem of irregular metal bombardment surface caused by the high dispersion of ion beam energy. The method can accurately and efficiently test the corrosion ability of ion beams on different metals, obtain the relative size of the corrosion resistance of different metal materials, and provide indicative significance for the selection of metal materials suitable for the nano-ion probe.
[0005] The first step is to make the metal material to be detected into a metal sample target.
[0006] The metal material to be tested is embedded in epoxy resin, the front and back target surfaces are polished, cleaned, dried, and subjected to low-temperature treatment to obtain the metal sample target.
[0007] The metal is selected from one or more of magnesium, gold, silver, tin, platinum, tantalum, vanadium, iron, bismuth, germanium, antimony, scandium, zinc, molybdenum, cobalt, chromium, tungsten, rubidium, zirconium, nickel, hafnium, osmium, iridium, palladium, copper, titanium, and neodymium.
[0008] The sample target is a circular epoxy resin target with a diameter of 0.5 to 1 inch and a thickness of 2 to 4 mm;
[0009] The front and back target surfaces are polished with diamond polishing paste.
[0010] The drying temperature is 60-80° C. and the drying time is 12-24 hours.
[0011] The low temperature treatment refers to placing the dried sample target at 5-15° C. for 1-5 hours.
[0012] The inventors discovered that after placing the sample target under low-temperature treatment, a certain temperature difference can be formed between the sample target to be tested and the test chamber. Therefore, when an ion beam is used to bombard the metal sample target to be tested, the temperature difference can reduce the instantaneous diffusion of heat generated by the ion beam, reduce the outward expansion of heat (or energy), improve the guarantee for subsequent ion beam focusing, and facilitate the generation of regular "cubic column" shaped erosion pits, which can quickly and accurately detect and analyze the corrosion resistance of different metals.
[0013] In one embodiment of the present invention, each metal material to be tested is embedded in epoxy resin, and the front and back target surfaces are polished with diamond polishing paste until all the metal materials to be tested on the front side are exposed and the surface is flat and scratch-free, and the back side is flat and not tilted. The sample target is ultrasonically cleaned with ultrapure water, and then the sample target is placed in a 70°C oven to dry for 24 hours, and then placed at 10°C for 2 hours to obtain the metal sample target.
[0014] In the second step, the metal sample target is detected and analyzed using a nano-ion probe.
[0015] The sample target is subjected to gradient vacuum treatment:
[0016] After the obtained sample target is sprayed with a carbon film, a vacuum treatment is performed to obtain three levels of vacuum conditions, namely, a first vacuum degree, a second vacuum degree and a third vacuum degree.
[0017] The carbon film has a thickness of 20-40 nm.
[0018] Preferably, the first vacuum degree<the second vacuum degree<the third vacuum degree.
[0019] More preferably, the first vacuum degree is (3-5)×10 -8 mbar;
[0020] The second vacuum degree is (4~8)×10 -9 mbar;
[0021] The third vacuum degree is (3~6)×10 -10 mbar;
[0022] Preferably, the sample target is placed in the first chamber at a first vacuum degree, the second chamber at a second vacuum degree, and the third chamber at a third vacuum degree, forming a low-medium-high gradient vacuum condition, which can effectively reduce the uneven heating range of the metal sample surface, avoid the thermal corrosion effect at the edge of the analysis area, improve the longitudinal corrosion accuracy, and obtain a more accurate measurement of the metal material's corrosion resistance.
[0023] Furthermore, the metal sample target is carbon-sprayed and placed in the chamber of NanoSIMS and evacuated to form low, medium and high vacuum conditions (corresponding to the first, second and third vacuum conditions respectively). The first, second and third vacuum conditions are obtained in the airlock, vessel and analysis chambers respectively; the airlock, vessel and analysis chambers are connected in sequence and separated by isolation valves; the low vacuum condition is (3~5)×10 -8 mbar, medium vacuum condition (4~8)×10 - 9 mbar, high vacuum condition is (3~6)×10 -10 Since high vacuum will inhibit the heat conduction effect, the present invention adopts low-medium-high gradient vacuum conditions to reduce the uneven heating range of the metal sample surface, avoid the thermal corrosion effect at the edge of the analysis area, improve the longitudinal corrosion accuracy, and obtain a more accurate metal material corrosion resistance.
[0024] In one embodiment of the present invention, first, a carbon film with a thickness of 30 nm is sprayed on the surface of the dried sample target, and then the sample target is placed in an airlock chamber and evacuated by a turbomolecular pump, and then the sample target is baked at 50°C with a halogen lamp until the vacuum drops to 5×10 -8 mbar, turn off the baking lamp, and after cooling, place the sample target in the vessel chamber and evacuate to 6×10 -9 mbar, the sample is placed in the analysis chamber and extracted by the ion pump to maintain the vacuum state at 5×10 -10 mbar.
[0025] Etching of metal sample target surface using oxygen primary ion beam:
[0026] An oxygen ion source is used to form a primary ion beam, and the primary ion beam intensity is adjusted; the primary ion beam is focused and made to vertically incident on the sample target surface to excite and generate secondary ions for scanning analysis.
[0027] The oxygen ion source condition is a radio frequency plasma oxygen source, which is generated by a Wien filter. 16 O - Primary ions;
[0028] The primary ion beam current intensity is 1~2nA;
[0029] The primary ion focusing includes energy focusing and direction focusing;
[0030] The spot diameter of the primary ion beam is 0.8~1.2μm;
[0031] The directional focusing conditions are: adjusting the bias voltage Oct90 of the octapole focuser to 15V~37V and the bias voltage Oct45 to -29V~-17V;
[0032] The energy focusing conditions are: the first pole immersion lens voltage is 8000V, the second pole immersion lens voltage is -8608~-8570V, and the third pole immersion lens voltage is 7281~7409V.
[0033] The primary ion focusing condition is important for the morphology of the etch pits on the sample. In one embodiment of the present invention, the primary ion beam current intensity for analysis is first adjusted to 1 nA, and the primary ion beam is focused by an octopole focuser and a second pole immersion lens to minimize the beam spot. The primary ion beam is given an accelerating voltage to vertically incident on the sample target surface to excite and generate secondary ions. A reverse voltage is applied to the first pole immersion lens to draw the secondary ions out of the sample surface, and the secondary ions are focused by a deflection plate and a third pole immersion lens, and the secondary ions are measured using the mass analyzer and the receiver.
[0034] The scanning analysis area can be set to 3 μm×3 μm to 15 μm×15 μm, with a resolution of 64×64 pixels, and an integration time of 0.541 seconds for scanning a complete frame.
[0035] The analysis time is 1 to 10 minutes.
[0036] The third step is to test the three-dimensional morphology of the metal sample target and obtain the longitudinal depth data of the erosion pit.
[0037] The three-dimensional morphology of the analysis area is tested to obtain longitudinal erosion pit depth data of the metal sample target in the analysis area.
[0038] The test is performed using a three-dimensional white light interferometer surface profiler.
[0039] The three-dimensional white light interferometric surface profiler comprises a measuring head, an object stage, a joystick and a computer.
[0040] Specifically: first place the metal sample target in the middle of the stage, adjust the joystick to align the sample under the eyepiece of the measuring head, open the white light interferometer measurement software on the computer, set the lowest point of the eyepiece downward on the software interface, and then fine-tune the distance between the lens and the surface of the sample target to be measured. After focusing, the white light interferometer performs sample scanning measurement, and save the data after the measurement is completed.
[0041] Then, the saved data was processed using NanoScope Analysis software. First, the three-dimensional morphology of the analysis area was obtained, and a measurement profile was set along the relatively flat direction of the bottom of the denudation pit in the analysis area, and then the data in the X and Y directions on the measurement profile were obtained, wherein the X direction represents the width change of the denudation pit (horizontally), and the Y direction represents the depth change of the denudation pit (vertically), and the X and Y data together outline the cross-sectional shape of the denudation pit in the direction of the profile.
[0042] Generally speaking, the size of X should be 1 to 1.4 times the horizontal length of the analysis area set above, which indicates that the scanned analysis area is reasonable; if it is larger than this range, there may be problems such as obvious outward expansion area, and the corresponding Y data cannot be used in the comparison of metal corrosion resistance.
[0043] The fourth step is to evaluate the corrosion resistance of the metal sample according to the longitudinal depth of the metal sample target corrosion pit.
[0044] The longitudinal depth values of the corrosion pits of the metal samples are counted and compared. The smaller the value, the stronger the metal's corrosion resistance is; conversely, the larger the value, the weaker the metal's corrosion resistance is; the corrosion resistance of the metals to be tested is ranked.
[0045] The present invention adopts means such as low-temperature pretreatment, gradient vacuum control and optimization of ion beam focusing conditions to reduce the outward expansion effect of the erosion pits in the analysis area caused by energy divergence, so that the erosion pits in the analysis area can all present a regular morphology similar to a "cubic column". Therefore, when the width in the X direction meets the corresponding range, only the depth of the erosion pit in the longitudinal Y direction can be considered, and the difference in the anti-erosion ability of different metals can be simply and efficiently evaluated, avoiding the occurrence of irregular "conical" erosion pits, which requires calculating the volume of pits in different X and Y directions, so as to compare the size of the metal anti-erosion ability, and effectively solves technical problems such as inaccurate calculation, large error, and complex process.
[0046] The beneficial effects of the present invention are:
[0047] 1. The present invention proposes a simple and direct way to evaluate the metal's anti-corrosion ability. The metal's anti-ion beam corrosion ability is affected by many factors, and the comparison of physical, chemical and other conditions alone cannot directly determine the magnitude of the corrosion resistance. The process of the present invention is simple and has a visual effect. The metal's anti-corrosion ability can be evaluated by measuring the vertical depth of the corrosion pit.
[0048] 2. The present invention forms a temperature difference in the test chamber by subjecting the target sample to low temperature pretreatment, which can reduce the instantaneous diffusion of heat generated by the ion beam and reduce the outward expansion, thereby facilitating the subsequent generation of regular "cubic column" shaped corrosion pits and improving the accuracy of metal corrosion resistance detection.
[0049] 3. The present invention improves the vacuum degree of the cavity, controls the appropriate gradient vacuum conditions, and optimizes the process of focusing the primary ion beam, thereby obtaining an accurate assessment of the metal's corrosion resistance. Since the energy and heat of the ion beam are Gaussian distribution characteristics, the metal will be locally expanded and melted due to the non-uniform bombardment and heating of the ion beam. By optimizing the vacuum degree of the cavity and presenting a suitable gradient difference, it is more conducive to suppressing the thermal effect, reducing the area of the thermal action area of the ion beam on the metal sample, and reducing the outward expansion of the corrosion pit caused by uneven heating. On the other hand, focusing the primary ion beam can concentrate its energy at the center of the ion beam, further reducing the outward expansion of the corrosion pit caused by energy divergence. Through the above operation, heat and energy can be concentrated in the center of the primary ion beam, so the corrosion resistance of the metal material can be judged only by the data of the Y direction of the corrosion pit, without considering the size of the X direction or the volume of the corrosion pit, making the entire operation process simpler, more intuitive and accurate. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0051] Figure 1 This is a schematic diagram of the metal material sample target described in Example 1;
[0052] Figure 2 This is a scan of the erosion pit morphology of the metal copper in Example 1 under oxygen ion beam conditions, wherein from left to right are a 2D morphology scan, a 3D morphology scan, and a depth / height scale of the erosion pit;
[0053] Figure 3 The scanning data of the etch pits of the metal copper in the oxygen ion beam in the X and Y directions in Example 1;
[0054] Figure 4 This is a scan of the erosion pit morphology of metal bismuth under oxygen ion beam conditions in Example 1, wherein from left to right are a 2D morphology scan, a 3D morphology scan, and a depth / height scale of the erosion pit;
[0055] Figure 5 The X and Y direction scanning data of the etched pit of metal bismuth under oxygen ion beam conditions in Example 1;
[0056] Figure 6 The results of the oxygen ion beam corrosion resistance of different metal samples described in Example 1;
[0057] Figure 7 The morphology of the etch pit of copper metal in comparative example 1 under oxygen ion beam conditions, the left picture is the 2D scanning morphology, and the right picture is the etch pit depth / height scale;
[0058] Figure 8 The X and Y direction scanning data of the etched pit of metal copper in comparative example 1 under oxygen ion beam conditions;
[0059] Fig. 9 The morphology of the etch pit of copper metal in comparative example 2 under oxygen ion beam conditions, the left picture is the 2D scanning morphology, and the right picture is the etch pit depth / height scale;
[0060] Fig.10 The X and Y direction scanning data of the etched pits of metal copper in comparative example 2 under oxygen ion beam conditions. DETAILED DESCRIPTION
[0061] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Generally, the components of the embodiments of the present invention described and shown in the drawings here can be arranged and designed in various different configurations.
[0062] The steps / operations in the present invention that do not specifically emphasize the temperature can be performed at room temperature, which is known to those skilled in the art and is generally 20-25°C.
[0063] Example 1
[0064] The first step is to make the metal material to be tested into a metal sample target: various metal samples, such as magnesium, gold, silver, tin, platinum, tantalum, vanadium, iron, bismuth, germanium, antimony, scandium, zinc, molybdenum, cobalt, chromium, tungsten, rubidium, zirconium, nickel, hafnium, osmium, iridium, palladium, copper, titanium, and neodymium, are embedded in epoxy resin, polished with diamond sand until all metals are exposed on the target surface without scratches, and the back of the target is polished until it is flat and without tilt. After washing with ultrapure water, the sample target is placed in a 70°C oven to dry for 24 hours, and then placed at 10°C for 2 hours to obtain the metal sample target. The diameter of the circular metal sample target is 1 inch and the thickness is 3 mm (such as Figure 1 as shown).
[0065] In the second step, the metal sample target is detected and analyzed using a nano-ion probe.
[0066] 2.1 The sample target was subjected to gradient vacuum treatment: First, a carbon film with a thickness of 30 nm was sprayed on the surface of the sample target, and then the metal sample target was sprayed with carbon and placed in the airlock chamber of NanoSIMS and vacuumed by a turbomolecular pump. The halogen lamp was turned on and baked at 50°C until the vacuum dropped to 5×10 -8 mbar, turn off the baking lamp, and after cooling, place the metal sample target in the vessel chamber and evacuate to 6×10 -9 mbar, and then put the sample into the analysis chamber and extract it through the ion pump to maintain the vacuum state at 5×10 -10 mbar.
[0067] 2.2 Use an oxygen ion source to form a primary ion beam and adjust the primary ion beam intensity; focus the primary ion beam and make it vertically incident on the sample target surface to excite and generate secondary ions for scanning analysis: use a radio frequency plasma oxygen source as the ion source for analysis to generate 16 O -The primary oxygen ion beam adjusts the beam energy of the primary ion beam to 1nA through the deflection plate, high-voltage lens and aperture, and focuses the primary ion beam using the octopole focuser and the second-pole immersion lens (high voltage -8572V), wherein the octopole focuser bias voltage Oct90 is 17V and Oct45 is -21V, and the beam spot diameter Ф of the focused primary ion beam is about 1μm; the secondary ions are drawn out through the reverse voltage of the first-pole immersion lens (high voltage 8000V), and are focused using the deflection plate and the third-pole immersion lens (high voltage 7304V) and analyzed by the mass spectrometry system, and the electron multiplier of the receiver part converts the electrical signal into a digital signal and presents it on the computer operation terminal.
[0068] The scanning analysis area was 10 μm×10 μm, and the analysis time was 5 minutes.
[0069] The third step is to test the three-dimensional morphology of the metal sample target and obtain the depth data of the longitudinal erosion pit: use the three-dimensional white light interferometry surface topography to obtain the three-dimensional morphology of the metal sample target analysis area, and measure the erosion characteristics of different metal sample analysis areas one by one. The above analysis conditions form erosion pits with flat bottoms on the samples. Then use NanoScopeAnalysis software to obtain the X- and Y-direction data of the measurement profile. This value can represent the depth of primary ion erosion on the metal.
[0070] The fourth step is to evaluate the corrosion resistance of the metal sample according to the longitudinal depth of the metal sample target corrosion pit: count and compare the longitudinal depth values of the metal sample target corrosion pit. The deeper the depth, the weaker the corrosion resistance of the sample, and the smaller the depth, the stronger the corrosion resistance of the sample; the corrosion resistance of the metals to be tested is ranked.
[0071] like Figure 2 As shown, from left to right are the 2D and 3D morphology images of metal copper in the conditional stripping pit of oxygen ion beam, and the depth / height scale of the stripping pit. Figure 3 It is the scanning data of the width X and depth Y direction of the erosion pit along the Aa measurement section line.
[0072] 2D and 3D images can intuitively show the effects of the erosion pits from the plane and side, and can further confirm that the regular erosion pits are cubic columnar in shape, where the X direction is the width change of the cubic columnar erosion pit along Aa, and the Y direction is the change in its depth. Figure 2 It can be seen that the erosion pits present a columnar structure (the blue area in 3D). The erosion pits in the X direction of the scanned area are relatively uniform and do not expand outward ( Figure 3 ), so only the vertical depth of the longitudinal direction Y can accurately characterize its ability to resist ion beam erosion, eliminating the calculation process of the full scan of the erosion pit volume.
[0073] Similarly, the erosion pits of bismuth metal are Figure 4 and Figure 5 As shown, it can also be seen that the erosion pits present a columnar structure in the scanning area ( Figure 4 3D blue area), the erosion pit morphology is uniform along the X direction of the Aa measurement profile ( Figure 5 ), so considering only the vertical depth in the longitudinal Y direction can accurately characterize its ability to resist ion beam erosion.
[0074] According to the figure, the Y depth of the metal copper is about 0.479μm ( Figure 2-3 ), the longitudinal Y depth of metal bismuth is about 1.8μm ( Figure 4-5 ), so it can be judged that the corrosion resistance of metallic copper is stronger than that of metallic bismuth.
[0075] According to the above method, the anti-corrosion ability of the 27 metal samples to be tested is ranked as follows: Figure 6 As shown, the metal iron has the strongest corrosion resistance, and the metal bismuth has the weakest.
[0076] Comparative Example 1
[0077] The anti-corrosion ability of metallic copper was tested. The testing process was the same as that of Example 1, except that in the first step, no low-temperature treatment was performed: the metallic copper was embedded in epoxy resin, and diamond polishing was performed until all metal was exposed on the target surface without scratches, and the back of the target was polished until it was flat and without tilt. After washing with ultrapure water, the sample target was placed in a 70°C oven and dried for 24 hours to obtain the copper sample target. The diameter of the circular copper sample target was 1 inch and the thickness was 3 mm.
[0078] The scanning analysis area was set to 3 μm × 3 μm, and the analysis time was 1 min. Figure 7 This is the 2D morphology of the metal copper etch pit conditioned by oxygen ion beam, where the white dotted line outlines the shape of the etch pit; Figure 8 The data of the width in the X direction and the depth in the Y direction are measured along the profile line Aa. It can be seen that the numerical uniformity in the X direction decreases, which is significantly lower than that in Example 1. The erosion pits show a slightly conical trend rather than a regular columnar structure. The depth in the longitudinal Y direction is about 0.24 μm ( Figure 8 ), indicating that the low-temperature treated samples have a certain inhibitory effect on the diffusion expansion. The volume of the erosion pits of the samples that have not been treated at low temperatures needs to be calculated, and only the depth in the longitudinal Y direction cannot be considered. Otherwise, the evaluation of the metal's anti-corrosion ability is not accurate and objective.
[0079] Comparative Example 2
[0080] The anti-corrosion ability of the metal copper is tested. The testing process is the same as that of Example 1, with the main difference being that the bias voltage of the octapole and the high voltage condition of the second pole immersion lens in the focusing condition in the second step are not within a reasonable range:
[0081] The bias voltage of the octapole focuser is 60V for Oct90 and -50V for Oct45, and the high voltage of the second pole immersion lens is -8050V. The scanning analysis area is set to 3μm×3μm, the analysis time is 1 minute, and other test conditions are the same as those in Example 1. The results are shown in Figure 9-10 As shown, Fig. 9 The 2D morphology of the metal copper in the oxygen ion beam conditional etch pit and the etch pit depth / height scale. Fig.10 It is the X-direction and Y-direction data along the Aa measurement section line. Fig. 9 The white dotted line in the middle shows the shape of the etch pit. Due to the poor focusing condition of the primary ion beam, irregular etch pits are generated on the surface of the copper sample. According to the scanning data ( Fig.10 ) It can also be seen that the erosion pit protrudes from the sample surface and the curvature of the bottom surface is extremely large, so it is impossible to estimate the erosion depth. At this time, it is also impossible to judge the strength of the metal copper's anti-erosion ability only by the Y-direction depth, and the error is large. This also shows that the focusing degree of the primary ion beam will affect the morphology of the erosion pit and cause inaccurate erosion depth measurement results, thereby affecting the accurate comparison of the metal's anti-erosion performance. Therefore, the high-pressure conditions of the octapole focuser and the second pole immersion lens are also crucial for accurately evaluating the metal's anti-erosion ability.
[0082] The above-described embodiments are only specific implementations of the present invention, which are used to illustrate the technical solutions of the present invention, rather than to limit them. The protection scope of the present invention is not limited thereto. Although the present invention is described in detail with reference to the above-described embodiments, ordinary technicians in the field should understand that any technician familiar with the technical field can still modify the technical solutions recorded in the above-described embodiments within the technical scope disclosed by the present invention, or can easily think of changes, or make equivalent replacements for some of the technical features therein; and these modifications, changes or replacements do not make the essence of the corresponding technical solutions deviate from the spirit and scope of the technical solutions of the embodiments of the present invention, and should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims.
Claims
1. A method for testing the corrosion resistance of metals, characterized in that: The steps include: The first step is to make the metal material to be tested into a metal sample target; The metal material to be tested is embedded in epoxy resin, the front and back target surfaces are polished, cleaned, dried, and subjected to low temperature treatment to obtain the metal sample target; The low temperature treatment refers to placing the dried sample target at 5-15°C for 1-5 hours; The second step is to use nano-ion probe to detect and analyze the metal sample target: 2.1 The metal sample target is subjected to gradient vacuum treatment: After the metal sample target is sprayed with a carbon film, it is subjected to vacuum treatment to obtain a first vacuum degree, a second vacuum degree, and a third vacuum degree respectively; the first vacuum degree < the second vacuum degree < the third vacuum degree; the first vacuum degree is (3~5)×10 -8 mbar; 2.2 Use oxygen primary ion beam to perform ablation on the surface of metal sample target: use oxygen ion source to form primary ion beam, and adjust the primary ion beam intensity; focus the primary ion beam and make it vertically incident on the metal sample target surface to excite and generate secondary ions for scanning analysis; The oxygen ion source condition is a radio frequency plasma oxygen source, generating 16 O - Primary ions; The primary ion beam current intensity is 1~2nA; The primary ion focusing includes energy focusing and direction focusing; The spot diameter of the primary ion beam is 0.8~1.2μm; The directional focusing condition is: adjust the bias voltage of the octapole focuser Oct90 to 15V~37V and Oct45 to -29V~-17V; The energy focusing conditions are: the first pole immersion lens voltage is 8000V, the second pole immersion lens voltage is -8608~-8570V, and the third pole immersion lens voltage is 7281~7409V; The third step is to test the three-dimensional morphology of the metal sample target and obtain the longitudinal depth data of the erosion pit; The fourth step is to evaluate the corrosion resistance of the metal sample according to the longitudinal depth of the metal sample target corrosion pit.
2. The testing method according to claim 1, characterized in that: In the first step, the metal is selected from one or more of magnesium, gold, silver, tin, platinum, tantalum, vanadium, iron, bismuth, germanium, antimony, scandium, zinc, molybdenum, cobalt, chromium, tungsten, rubidium, zirconium, nickel, hafnium, osmium, iridium, palladium, copper, titanium, and neodymium; The metal sample target is a circular epoxy resin target with a diameter of 0.5 to 1 inch and a thickness of 2 to 4 mm; The drying temperature is 60-80° C. and the drying time is 12-24 hours.
3. The testing method according to claim 1, characterized in that: The second vacuum degree is (4~8)×10 -9 mbar, the third vacuum degree is (3~6)×10 -10 mbar.
4. The testing method according to claim 3, characterized in that: After the metal sample target is sprayed with a carbon film, it is placed in the chamber of NanoSIMS and evacuated to form the first, second and third vacuum conditions; the first, second and third vacuum conditions are respectively obtained in the three chambers of airlock, vessel and analysis; the three chambers of airlock, vessel and analysis are connected in sequence and separated by isolation valves.
5. The testing method according to claim 1 or 2, characterized in that: In step 2.2, the scanning analysis area is set to 3 μm × 3 μm to 15 μm × 15 μm, and the analysis time is 1 to 10 minutes.
6. The testing method according to claim 1 or 2, characterized in that: In the third step, a three-dimensional white light interferometer surface profiler is used to test the three-dimensional morphology of the analysis area to obtain longitudinal erosion pit depth data of the metal sample target in the analysis area; In the fourth step, the longitudinal depth values of the target erosion pits of the metal samples are counted and compared, and the corrosion resistance of the metals to be tested is ranked.
7. The testing method according to claim 6, characterized in that: In the third step, first place the metal sample target in the middle of the stage, adjust the joystick, open the white light interferometer measurement software, focus the white light interferometer to perform sample scanning measurement, and save the data after the measurement is completed; Then, the stored data is processed using NanoScope Analysis software to obtain a three-dimensional topography of the analysis area, a measurement profile is set along a relatively flat direction of the bottom of the erosion pit in the analysis area, and data in the X and Y directions on the measurement profile are obtained.
8. Application of the test method according to any one of claims 1 to 7 in evaluating the corrosion resistance of metal to nano-ion probes.
Citation Information
Patent Citations
Preparation method of secondary ion probe sample target
CN108375497A
Method for representing three-dimensional microstructure of ceramic coating material based on focused ion beam
CN113390914A